Neutrophil Lymphocyte Ratio, Three Year Survival of Locally Advanced and Advanced Nasopharyngeal Carcinoma - Cahyanur, Rahmat; Nufus, Hayatun; Irawan, Cosphiadi (Jurnal Penyakit Dalam Indonesia, 2021)
Introduction. Nasopharyngeal carcinoma (NPC) is the most prevalent head and neck malignancy in Indonesia, as NPC-related mortality in Indonesia is the second-highest in Asia after China. Inflammation has been studied to be associated with cancer progression. Neutrophil lymphocyte ratio describes the balance between the unfavorable suppression of immune response against cancer by neutrophils and the beneficial effect of adaptive immunity by lymphocytes. This study aimed to determine the relationship between NLR and the survival of locally advanced and advanced NPC patients.Methods. A retrospective cohort study was conducted using the medical records of NPC patients treated at the hematology clinic RSCM from 2015 to 2018. The difference in 3-year survival between NPC patients with and without metastasis, also high and low NLR, was analyzed with the Kaplan-Meier method. At the same time, multivariate Cox regression analysis was used to obtain adjusted hazard ratios (HR) after comparing with patients’ age, gender, T stage, N stage, NLR level, and metastasis status.Results. There were 143 patients included in this study; a total of 49 (34.3%) had metastasis. There was a significant difference in survival between those with and without metastasis (p=0.001), with 3-year survival of 24.5% in patients with metastasis. The AUC of NLR was 0.600 (CI 95% 0.502—0.698; p=0.049). The optimal cut-off value determined for NLR was 4.7 with a sensitivity of 56.00%, specificity of 62.37%, PPV of 59.81%, and NPV of 58.64% in predicting survival. Based on that value (≥4,7), there was a significant difference in proportion between those with and without metastasis (63.3% vs. 33.0%, p=0.001). Multivariateanalysis showed that metastasis (HR 3.349, CI 95% 1.909—5.874, p<0.001) was associated with poorer survival.Conclusions. There was no association between NLR and 3-year survival in NPC patients. The proportion of subjects with high NLR was found higher in those with metastasis. Metastasis status was associated with 3-year survival.